Novos direitos: poder judiciário e o direito dos idosos a uma vida digna. O caso da saúde - Caldeira, Andrize Leite (Universidade do Vale do Rio do Sinos, 2009)
This paper will address the social role of the judiciary in implementing the right to health of the elderly as major social actors in search of realization of these rights, it being understood that as a human right, fundamental and social. Together with other political and social, the Judiciary is the guarantor of that law which is constitutionally provided for and which should be construed to hold the citizenship, that is, not forgetting the substance and the values he represents to be enforce the dignity and democratic state of law. Thus, the work unfolds in a first part, that the right of the elderly to health is a fundamental human right, constitutional and social as well as others of the same species, can be considered "new" rights. Although the first part of the study showed that there are social actors, with its symbolic power, is responsible to implement this law. In the second part of the work and the third chapter, we discuss the importance of the Judiciary in the effectiveness of those rights of th
Keywords: dignidade; idoso; novos direitos; saúde; poder judiciário; dignity health; elderly; new rights; judiciary; Ciências Sociais Aplicadas